Management of COVID-19 waste in a health facility in Ghana - Senam, Tengey; Rockson, Mizpah Ama Dziedzorm (International Journal Of Community Medicine And Public Health, 2020)
Background: COVID-19 which has been declared a global pandemic by the World Health Organization (WHO) has affected most countries in the world including Ghana. The first positive case of the disease was confirmed in Ghana on 12th March, 2020 and since then, its number has increased to over 566 as at the end of the study period. The aim of the study was to assess how one of the health facilities manages waste materials generated from COVID-19 patients. Methods: The study lasted for four weeks within which various interviews, independent observations, waste measurements and data analysis with Microsoft Excel were made. A purposive sampling technique was used to select one health facility for this study. Results: The facility allocated 36 beds for the COVID-19 patients. A total of 178.80 kg of infectious waste was generated within the four weeks. Waste from the isolation units were placed in bins lined with red bags and plastic sharps containers. The hazardous waste from the facility is finally collected and transported by a private waste medical waste management company for safe treatment and disposal. Conclusions: The study concluded that, the health facility practiced proper infection prevention and control (IPC) practices at the COVID-19 isolation centre. The study recommends that, awareness should be created for hazardous waste in general through training and advocacy. More centralized medical waste treatment facilities should be established in other parts of the country and there should also be strict enforcement of policies and regulations on healthcare waste management.